2019
DOI: 10.3390/s19122672
|View full text |Cite
|
Sign up to set email alerts
|

WePBAS: A Weighted Pixel-Based Adaptive Segmenter for Change Detection

Abstract: The pixel-based adaptive segmenter (PBAS) is a classic background modeling algorithm for change detection. However, it is difficult for the PBAS method to detect foreground targets in dynamic background regions. To solve this problem, based on PBAS, a weighted pixel-based adaptive segmenter named WePBAS for change detection is proposed in this paper. WePBAS uses weighted background samples as a background model. In the PBAS method, the samples in the background model are not weighted. In the weighted backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…To solve the above problems, a trust interval was set to judge if the current background model is suitable to update under the current traffic conditions. The interval was generated by the pixel-based adaptive segmentation algorithm [30], which automatically updates threshold R(x,y) and learning rate T(x,y) with the dynamic changes of the background. The background model B(x,y) can be defined as:…”
Section: Vehicle Detection Based On Multi-frame Intervalmentioning
confidence: 99%
“…To solve the above problems, a trust interval was set to judge if the current background model is suitable to update under the current traffic conditions. The interval was generated by the pixel-based adaptive segmentation algorithm [30], which automatically updates threshold R(x,y) and learning rate T(x,y) with the dynamic changes of the background. The background model B(x,y) can be defined as:…”
Section: Vehicle Detection Based On Multi-frame Intervalmentioning
confidence: 99%
“…Comparison is done on the basis of two stages model. First stage is used to generate binary mask using background subtraction model and compare with ve state of the art methods (i) Temporal Average Filter [5], (ii) Running Average Gaussian (RAG) [22], (iii) Adaptive GMM [23], (iv) WePBAS [29], (v) ViBe [27]. These methods are chosen on the requirement of mapping threshold value for foreground segmentation.…”
Section: Comparisons Of Qualitative Results Of Proposed Background Su...mentioning
confidence: 99%
“…Table 5 and Table 6 represent quantitative analysis of proposed method after post processing operations and observe that proposed method is able to generate better results than compared methods. There are few frames in Highway dataset which are associated with shadow due to which AGMM [23], WePBAS [29], and ViBe [27] methods generate more pixels misclassi cations (considering shadow pixels as foreground) and increases more false positive rate (FPR). It is observed that in Highway dataset, RAG [22] shows bad recall when more pixels are misclassi ed due to long shadow.…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation